Analysis of Numeracy Literacy Activities of PGSD Students Through Writing Mathematics A Month - Ema Butsi Prihastari; Kastono Kastono (Universitas Negeri Makassar, 2022)
This study maps numeracy-based mathematics material through mathematics writing activities for 30 days. There are 4 (four) components of numeracy literacy, namely algebra, numbers, geometry and measurement, and data and uncertainty. This type of research is a case study with a qualitative descriptive approach. The research subjects are PGSD students in the fourth semester of the 2021/2022 Academic Year who have taken the Introduction to Basic Mathematics and Geometry and Measurement courses in elementary schools comprising of 3 classes. Data collection techniques use observation, interviews, and documentation with data analysis techniques, namely a) data collection, b) data condensation, c) data presentation, and d) data verification. To guarantee the correctness of the results of the study, techniques are carried out: a) the persistence of observers, which is carried out seriously and continuously and b) triangulation. The results of the study found that the material, that most students presented in mathematics writing activities was Geometry and Measurement with an average percentage of 46.5%, because it was found in many daily lives and was easy to describe in writing. Meanwhile, with an average percentage of 1.67% in Algebraic material which is the least written material for students because it requires accuracy in determining variables.